Early treatment with high-potency statins in patients with acute coronary syndrome—an example of personalized medicine - Harari, Emanuel; Eisen, Alon (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Statins, together with aspirin, are the cornerstone of secondary prevention treatment in stable coronary artery disease (CAD) and acute coronary syndrome (ACS). The Myocardial Ischemia Reduction with Aggressive Cholesterol Lowering (MIRACL) study was one of the first randomized controlled trials which demonstrated a benefit of high-potency statin therapy in the setting of ACS (1).